Pembangunan Prototaip Aplikasi Java Untuk Sistem Pengeluaran - Mohd. Nazri, Saad (2001)

(untitled)
This project is under Graduate School to complete the MSc.lT program. This project title is building the prototype of Java application in production system database. First at all this project will determine the basic concept of production system design and analysis whereby to capture the area of business activities and to give some solution in the area of production system database. That means this project can proceed the newest technology in system database design like Java application. After that this project can show the effectiveness of Java language using in the database system especially in Java 2 software. That means this project also defined and determines useful of Java language such as graphical analysis, embedded database and networks capabilities. This project also captured all of production database needed and the solution is the Java programming language. I hope this project can give the newest database technology development especially in the production environment.